Differences in Virulence Between Bovine-Derived Clinical Isolates of Pasteurella multocida Serotype A from the UK and the USA in a Model of Bovine Pneumonic Pasteurellosis. Issue 1 (July 2016) - Dagleish, M.P.; Bayne, C.W.; Moon, G.G.; Finlayson, J.; Sales, J.; Williams, J.; Hodgson, J.C.
Summary: The time of onset and subsequent degree and progression of clinical signs, bacterial colonization and tissue pathology during experimental disease induced by intratracheal inoculation of either a UK or USA isolate of Pasteurella multocida serotype A recovered from clinical cases of bovine pneumonia were determined. Calves aged 8 weeks were challenged with 300 ml phosphate buffered saline (PBS) alone (group 1, n  = 3, negative control) or containing 7.1 × 10 8 colony forming units (cfu) of UK isolate (group 2, n  = 8) or 5.8 × 10 8  cfu of USA isolate (group 3, n  = 8). Bronchoalveolar lavage (BAL) at 0, 1 and 4 days post challenge (dpc) and at the time of necropsy examination (7–8 dpc) showed no significant differences between groups 2 and 3 in bacterial numbers recovered. No P. multocida were recovered from group 1 animals. No clinical disease was present in group 1 calves and in group 3 was limited to scour in 1 calf at 1 dpc. All calves in group 2 had reduced food intake at 4–5 dpc, five had periods of dullness, three a mild nasal discharge at 1 dpc, four had mild to substantial respiratory stridor and one was killed at 6 dpc for humane reasons. Rectal temperatures remained about 39°C in group 1 calves, but increased in P. multocida -challenged calves to 40–41°C within 8–12 h of challenge. Significantly ( P  = 0.01) greater percentages of lung surface area were consolidated in group 2 (mean ± SD, 21 ± 10.1) compared with group 3 (7 ± 8.6) calves. Significantly more extensive and severe histological lesions were present in the lung lobes ( P  = 0.006) and lymph nodes ( P  = 0.02) of group 2 compared with group 3 calves. Pleurisy was present in group 2 calves only and no pathology was present in group 1. Pulsed-field gel electrophoresis (PFGE) produced 11 (group 2, UK isolate) or 10 (group 3, USA isolate) bands with differences in banding patterns. Results overall showed that two isolates, distinct geographically and genetically (by PFGE), caused pneumonic pasteurellosis in a single host with significantly different severity of pathology. This information is relevant to the development of novel vaccine control and interpretation of diagnostic results.